Dampak dari Kebangkitan Yesus Kristus (Studi Analisis Yohanes 20:19-23) - Sihombing, Warseto Freddy (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Abstract: Fear is caused by many things and makes everyone not dare to do anything and prefer to lock himself up. This’s what happened to Jesus' disciples after the story of crucifixion. An analytical study of the text in John 20:19-23 provides an evidence of the condition of the disciples and how Jesus, after rising from the dead, came to meet them. In their case, Jesus preached and gave peace to His disciples. They also breathed with the Holy Spirit and given a commission as apostles that they should preach forgiveness of sins’ news in the only begotten Son of God to the world.Keywords: fear, peace, forgiveness of sinsAbstrakRasa takut disebabkan oleh banyak hal dan menjadikan seseorang tidak berani bertindak apa-apa dan lebih memilih mengurung diri. Hal ini lah yang terjadi pada murid-murid Yesus setelah peristiwa penyaliban. Studi analisis terhadap teks dalam Yohanes 20:19-23 memberikan sebuah bukti keadaan para murid waktu itu dan bagaimana Yesus, setelah bangkit dari antara orang mati datang menemui mereka. Dalam ketakutan mereka, Yesus memberitakan dan emberikan damai sejahtera kepada murid-murid-Nya. Mereka juga diembusi dengan Roh Kudus dan diberikan sebuah amanat sebagai para rasul yang harus memberitakan berita tentang pengampunan dosa dalam Anak Tunggal Allah kepada dunia.Kata kunci: takut, damai sejahtera, pengampunan dosa